Food Security is A Determinant of Anemia in Children Aged 6 – 23 Months at UPTD Puskesmas DTP Pedes - Wahyuningsih, Utami; Rohmah, Lulu Mamluatur; Simanungkalit, Sintha Fransiske; Arini, Firlia Ayu (Journal of Global Nutrition, 2024)
In 2019, WHO data showed that the prevalence of anemia in children aged 6-59 months in Indonesia was 38.4%. The impact of anemia in children under two years old causes permanent cognitive damage and increases the risk of death. Objective: This study aims to determine the factors associated with anemia in children aged 6-23 months. Methods: This type of research is an analytic observational study with a cross-sectional design. The accidental sampling method was used to obtain 100 respondents who fit the inclusion and exclusion criteria. The study was conducted with a questionnaire instrument and Hb examination using the Easytouch GcHb tool. Data analysis included univariate, bivariate, and multivariate. Results: variables associated with anemia in under two are maternal education (p = 0.003), maternal age (p = 0.042), maternal knowledge (p = 0.004), maternal parenting (p = 0.003), and food security (p = 0.003). After multivariate test, it was found that food security was the dominant factor of anemia in children with OR 10.052. Conclusion: Food security is the dominant factor in children's anemia status with a 10.052 times higher potential for anemia. Food insecurity is related to changes in food quality that can affect the availability of nutrient-dense foods, including foods with high iron bioavailability. This can lead to anemia through inadequate micronutrient intake. The government should conduct early detection of anemia in children so as to prevent anemia as early as possible and provide non-cash food assistance to communities experiencing food insecurity